A twist of fate: How a meiotic protein is providing new perspectives on germ cell development. Issue 2 (2nd April 2016) - Mainpal, Rana; Yanowitz, Judith L.
ABSTRACT: The molecular pathways that govern how germ line fate is acquired is an area of intense investigation that has major implications for the development of assisted reproductive technologies, infertility interventions, and treatment of germ cell cancers. Transcriptional repression has emerged as a primary mechanism to ensure suppression of somatic growth programs in primordial germ cells. In this commentary, we address how xnd-1 illuminates our understanding of transcriptional repression and how it is coordinated with the germ cell differentiation program. We recently identified xnd-1 as a novel, early determinant of germ cell fates in Caenorhabditis elegans . Our study revealed that XND-1 is maternally deposited into early embryos where it is selectively enriched in the germ lineage and then exclusively found on chromatin in the germ lineage throughout development and into adulthood when it dissociates from chromosomes in late pachytene. This localization is consistent with a range of interesting germ cell defects that suggest xnd-1 is a pivotal determinant of germ cell characteristics. Loss of xnd-1 results in a unique "one PGC (primordial germ cell)" phenotype due to G2 cell cycle arrest of the germline precursor blastomere, P4, which predisposes the animal and its progeny for reduced fecundity. The sterility in xnd-1 mutants is correlated with an increase in the transcriptional activation-associated histone modification, dimethylation of histone H3 lysine 4 (H3K4me2), and aberrant expression of somatic transgenes but overlapping roles with nos-2 and nos-1 suggest that transcriptional repression is achieved by multiple redundant mechanisms.